PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI MTsN 1 ACEH UTARA - Zakiyanti, Mutia (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
The problem raised in this CAR is whether the application of the Problem Based Instruction (PBI) Learning Model can improve student learning outcomes in Indonesian Language Learning Challenge Text Materials for Class IX/1 at MTsN 1 Aceh Utara. The problem solving used is in the form of classroom action research. The action was carried out in 2 cycles, each cycle consisting of 2 meetings, each meeting consisting of preliminary activities, core activities and closing activities. This article is equipped with theory and research methods along with the required instruments. The theory presented is related to Indonesian Language Subjects with Challenge Text Materials through the Problem Based Instruction (PBI) Learning Model. This article is equipped with observation instruments relating to the behavior of students in the learning process and observation instruments for teachers both observing the lesson plans and actions in the learning process. After taking action from 2 cycles consisting of 4 meetings, data were found which were the results of observer observations. After the data was discussed/analyzed, it was concluded that with the application of the Problem Based Instruction (PBI) learning model, student learning outcomes towards Indonesian Language Learning Challenge Text Materials in Class IX/1 MTsN 1 North Aceh showed an increase from cycle I to cycle II, where the results the final score is above the minimum standard (76%) which is 90.7%. Furthermore, the researcher submits the following recommendations; Teachers should prepare, design learning for students who have not reached the Minimum Completeness Criteria (KKM) using effective methods.